INICIATIVAS CIENTÍFICAS NA EDUCAÇÃO INFANTIL: IDENTIFICANDO LIMITES E POTENCIALIDADES - Dias, Márcia Denise Beck (2019)
This research is linked to the Graduate Program in the Teaching of Science and Mathematics at the Professional Master’s Degree level of the Franciscan University. The objective was to understand how the experimental activities which were developed in a Municipal School of Early Childhood Education fostered science education in childhood in line with the demands of the National Common Curriculum Base. It also aimed to create an educational product in order to promote teacher education. This research follows a qualitative approach based on the bibliography and documentary methods of analysis. Among the materials analysed were 11 works presented at a Science Fair, which was held at the Municipal School of Early Childhood Education in 2017. Based on Bardin (2011), five pre-established categories of analysis were chosen in order to show how these works were aligned with the Fields of Experience proposed by the National Common Curricular Base (BRAZIL, 2017). These categories are: The self, the other and us; Body, gestures and movement; Traces, sounds, colours and shapes; Listening, speaking, thinking and imagination; and Spaces, times, quantities, relationships and transformations. As a result, it was noticed that three of the works presented at the Science Fair introduced concepts from the area of Natural Sciences, involving simultaneously the five Fields of Experience recommended by the National Common Curriculum Base. Therefore, it is noteworthy that, in Early Childhood Education, it is also possible to have, experience and promote in children a taste for science through concrete and experimental activities as well as to develop the teaching of Natural Sciences by permeating the five Fields of Experience previously mentioned. Given the data collected and analysed, it was possible to identify the potentialities and weaknesses of the activities developed in the school, which, in turn, demands new actions by the teachers towards continuing education. Thus, as a result of this research, an educational product has been developed, that is, a teacher training course called “Management of Scientific Initiatives in Childhood”, which aims to provide opportunities for continuing education for teachers focused on scientific education in childhood. This is an opportunity to promote teacher education in the face-to-face modality, which includes the theme, general objective, justification, contents to be studied and deepened, ways to systematize the proposed activities and complementary information. Based on this study, it was found that experimental activities can be developed in Early Childhood Education in a playful and concrete way, thus triggering children’s particularities such as curiosity and imagination. However, continuing education for teachers, especially in the field of Natural Sciences, is necessary.